the expression=
![3\sqrt[]{6}\text{ = 7,348}](https://img.qammunity.org/2023/formulas/mathematics/college/dmzhh0rjxkk2gir5scv1tm871yow1pkoed.png)
Like we did before, let's check first solving them
A. sqrt 27 x sqrt 2= 7,348 this one is correct
B. sqrt 9x sqrt 6= 7,348 this one is correct
C. sqrt 27 x sqrt 4= 10,39 no
D. sqrt 54= 7,348 this one is correct
E. sqrt 18= 4,24 no
F. 54 no
And now we apply properties to explain why they are the same expression
A=
![\sqrt[]{27}\cdot\sqrt[]{2}=\sqrt[]{27\cdot2}=\sqrt[]{54}=\sqrt[]{9\cdot6}=\sqrt[]{9}\cdot\sqrt[]{6}=3\cdot\sqrt[]{6}](https://img.qammunity.org/2023/formulas/mathematics/college/fjli8t7j2fwix0f3xhiuts2z1z83v71zou.png)
note= to the 9 x 6, what I did was divide 54 by the number on the sqrt on the expression (6)
B=
![\sqrt[]{9}\cdot\sqrt[]{6}=3\cdot\sqrt[]{6}](https://img.qammunity.org/2023/formulas/mathematics/college/drydqryd9xl1gzrzf45cg01l4ciavl47v0.png)
and the last one
D=
![\sqrt[]{54}=\sqrt[]{9\cdot6}=\sqrt[]{9}\cdot\sqrt[]{6}=3\cdot\sqrt[]{6}](https://img.qammunity.org/2023/formulas/mathematics/college/lwt44h2d67g2cfep7596tdu2561et3dy9s.png)